High Seroconversion Rate Against Severe Acute Respiratory Syndrome Coronavirus 2 in Symptomatic Pediatric Inflammatory Bowel Disease Patients. Issue 3 (24th September 2021) - Ruan, Wenly; Nguyen, Huyen; Wyatt, Allyson; Ihekweazu, Faith; Vartabedian, Bryan S.; Karam, Lina; Walsh, Seema; Kellermayer, Richard
Abstract : ABSTRACT: Understanding coronavirus disease 2019 (COVID-19) in pediatric inflammatory bowel disease (PIBD) is important. We describe a single-center cohort of COVID-19 PIBD patients where seroconversion against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was examined. Immunosuppressed PIBD patients at Texas Children's Hospital who tested positive for SARS-CoV-2 by nasopharyngeal reverse transcriptase polymerase chain reaction were included in the study. The clinical course of IBD, concurrent medications, COVID-19 related symptoms, SARS-CoV-2 testing date, and SARS-CoV-2 immunoglobulin G (IgG) antibody testing date and result were examined. Of 14 SARS-CoV-2 positive PIBD patients, 12 were tested for qualitative anti-SARS-CoV-2 IgG (seven with transient COVID-19 symptoms, five asymptomatic). All symptomatic (7/7) and 60% of asymptomatic (3/5) patients seroconverted. No patients required hospitalization attributed to COVID-19. High rates of COVID-19 seroconversion occurred in immunosuppressed and symptomatic PIBD patients. More research to evaluate the significance of COVID-19 seroconversion is needed.